Validation of the Spanish adaptation of the School Atitude Assessment Survey-Revised using multidimensional Rasch analysis - Veas, Alejandro; Castejón, Juan Luis; Gilar, Raquel; Miñano, Pablo (Anales de Psicología / Annals of Psychology, 2016)
The School Attitude Assessment Survey-Revised (SAAS-R) was developed by McCoach & Siegle (2003b) and validated in Spain by Author (2014) using Classical Test Theory. The objective of the current research is to validate SAAS-R using multidimensional Rasch analysis. Data were collected from 1398 students attending different high schools. Principal Component Analysis supported the multidimensional SAAS-R. The item difficulty and person ability were calibrated along the same latent trait scale. 10 items were removed from the scale due to misfit with the Rasch model. Differential Item Functioning revealed no significant differences across gender for the remaining 25 items. The 7-category rating scale structure did not function well, and the subscale goal valuation obtained low reliability values. The multidimensional Rasch model supported 25 item-scale SAAS-R measures from five latent factors. Therefore, the advantages of multidimensional Rasch analysis are demonstrated in this study.